Utilização do sistema de bioflocos na larvicultura de Tilápia-do-Nilo - Serafini, Raphael de Leão [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
There is a tendency of intensification of aquaculture production systems with the increase in global fish demand. Amongst the intensive aquaculture systems, the biofloc system has been gaining more importance because it is a relatively simple system comparing to the recirculation aquaculture system (RAS), and enables to optimize the use of water resources. The biofloc system is currently widely studied and applied in marine shrimp culture and in tilapia grow out, but the adoption of this technology in larviculture of freshwater fish is still a new subject and scarcely evaluated. The aim of this study was to evaluate different aspects for utilization of this technology during the larviculture of Nile tilapia. Four experiments were performed to evaluate the following issues: time of maturation of the biofloc system before the larvae stocking; use of artificial substrate; daily molasses addition; stocking density; different carbon sources and C/N ratio. In synthesis, the biofloc system was quite efficient for the production of juvenile tilapia in static systems without water exchange, promoting good growth rate and survival of larvae and a better use of the aquafeeds (feed convention ratio more efficient). Using an inoculant containing biofloc water already established dispenses the preparation of tanks prior to larval stocking, optimizing the production units (tanks and ponds) of fish farming. The use of artificial substrates did not promote any benefit in maintenance of the water quality parameters and performance of larvae reared in the biofloc system. The daily molasses addition in tanks improved the larval survival rates. The estimated maximum stocking density that can be used in this low-scale system is up to four larvae per liter. Different organic carbon sources can be used to promote the development of heterotrophic bacteria important for maintenance of this system. Further work should be carried out to assess the use of this ...

Com o aumento da demanda mundial de pescado surge uma tendência de intensificação dos sistemas produtivos de criação de organismos aquáticos. Entre os sistemas intensivos de aquicultura, o sistema de bioflocos vem ganhando cada vez mais espaço por ser um sistema relativamente mais simples do que o sistema de recirculação de água e capaz de otimizar a utilização dos recursos hídricos. Apesar do sistema de bioflocos ser atualmente bastante estudado na carcinicultura marinha e na fase engorda de tilápia, a adoção dessa tecnologia na larvicultura de peixes de água doce ainda é um assunto novo e pouco avaliado. O objetivo deste trabalho foi avaliar o efeito de diferentes variáveis de manejo na larvicultura de tilápia-do-nilo neste sistema de criação. Foram realizados quatro experimentos que avaliaram: o tempo de maturação do sistema de bioflocos antes do povoamento das larvas; a utilização de substrato artificial e a adição diária de melaço; a densidade de estocagem das larvas; e diferentes fontes de carbono e relações entre carbono e nitrogênio. Em síntese, o sistema de bioflocos foi eficiente para a produção de juvenis de tilápia em sistemas estático sem a renovação de água, promovendo boa taxa de crescimento e sobrevivência das larvas e melhor aproveitamento da ração (conversão alimentar aparente mais eficiente). A utilização de um inóculo de água contendo bioflocos já estabelecido permite a dispensa de preparo prévio dos tanques de criação anteriormente ao povoamento das larvas, otimizando desta forma as unidades de produção (tanques e viveiros) da piscicultura. A utilização de substratos artificiais não promoveu nenhum beneficio na manutenção dos parâmetros de qualidade de água e no desempenho das larvas criadas no sistema de bioflocos. A adição diária de melaço nos tanques proporcionou melhores...
Keywords: Peixe; Tilápia-do-Nilo; Desempenho; Peixe - Larva; Água - Qualidade; Water quality